The Authority of Desert People in Classical Grammarians’ Studies - Al-Osaily, Eiad Fathi; Alzu’bi, Moath Haza’; Shalan, Sanaa Kamel; Talafha, Ahmad Saleh (Dirasat: Human and Social Sciences, 2024)
Objectives: This research explores how classical grammarians drew upon desert people’s speech traditions to establish grammatical rules, emphasizing the significance of this linguistic reference in terms of matrix, essence, and objective. The study examines the phenomenon of citing and occasionally challenging desert people’s speech, leading to an exploration of the grammarians’ divided perspectives, particularly regarding its origins. Methods: The study investigated desert people’s traits mentioned in the Arabic tradition, weighing the contradictions. It also referred to grammarians’ methods of citing desert people following the contextual analysis approach. Results: The study suggests that Arabic tradition indulgently overlooked the difference between desert people and Bedouins. It distinguishes the two and presents evidence to establish the differences. It holds that the grammarians’ communication with desert people, for what they believed to be of benefit for their studies, is a practice common among Basra’s grammarians and linguists of the fourth class, suggesting that likelihood that they started the practice. It demonstrates that classical grammarians, regardless of their approaches to citing, or sometimes denying, desert people’s speech, limited themselves to it, hence developing their linguistic schools and methods. Conclusions: This study challenges the equivalence of "desert people" and "Bedouins," highlighting historical distinctions. It asserts that classical grammarians employed specific criteria when referencing desert people’s speech: if it aligned with their approaches, it served as a model; otherwise, they deemed it weak evidence. It concludes by noting the heightened status of desert people post-Quran, with some scholars emulating them to be recognized as a "desert person."